FLUNITRAZEPAM SEBAGAI RAPE DRUG PADA KASUS PEMERKOSAAN - Nandita, Putu Nandya (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 9 No 2 (2019): Indonesian Journal of Legal and Forensic Sciences, 2019)
Rape drugs are drugs that are sometimes used for sexual abuse such as rape. Rape drug that is often misused in cases of rape is flunitrazepam or better known as "rohypnol". Flunitrazepam is the benzodiazepine class of compounds, flunitrazepam effect varies depending on the dose administered, the resulting effects ranging from sedation to coma stage four. In reviewing this article we will summarize the cases of misuse of flunitrazepam in Indonesia, pathways for the synthesis of flunitrazepam, pharmacological effects, pharmacokinetics and pharmacodynamics of flunitrazepam and forensic toxicology analysis in cases of abuse of flunitrazepam compounds.